THE USE OF NOUN PHRASE IN SCIENTIFIC SENTENCE - ZANDROTO, WENI AYU SUNITA; LUBIS, NURAINI ADE PUTRI; PANGARIBUAN, WANAPRI; MUDJISUSATYO, YUNIARTO (Universitas Negeri Medan, 2024)
The purpose of this research is to identify the types and patterns of the noun phrase. The aim of this research is to identify the types and patterns of word combinations that form noun phrases in journal articles published by BJA educational article with the title